Oxidation of vacuum residue by ozone and nitrous oxide: FTIR analysis - Sahua M.K.; Tewarib K.; Sinhaa A.S.K. (My University, 2025)
Vacuum residue is crude oil fraction obtained at the bottom of vacuum distillation column having boiling point above 565°C. Vacuum residue is often used without further treatment as fuel oil or for the production of asphalt. Ozone (O3) is a triatomic allotrope of oxygen and is an extremely strong oxidizing agent. It can cleave and oxidize benzene and other aromatic structures including PAHs. Nitrous oxide is also a good oxidizing agent relate to a particular state of anion radicaloxygen species Oα -(called α-oxygen), which forms on α sites from N2O. Liquid phase oxidation of vacuum residue at temperature 100-150°C either ozone or nitrous oxide results into conversion of the residue to oxygenated hydrocarbons.This process reduces concentration of aromatics and olefins which are known to be coke precursors in reforming application. The reaction of oxidant with vacuum residue has been investigated in detail using FTIR.